Impact of treatment adherence on efficacy of dolutegravir plus lamivudine and dolutegravir plus tenofovir disoproxil fumarate/emtricitabine: pooled analysis of the GEMINI-1 and GEMINI-2 clinical studies. Issue 1 (9th December 2021) - Ait-Khaled, Mounir; Sierra Madero, Juan; Estrada, Vicente; Gulminetti, Roberto; Hagins, Debbie; Tsai, Hung-Chin; Man, Choy; Sievers, Jörg; Grove, Richard; Zolopa, Andrew; Wynne, Brian; van Wyk, Jean
Abstract: Background: GEMINI-1 and GEMINI-2 (ClinicalTrials.gov, NCT02831673 and NCT02831764, respectively) are double-blind, multicenter, phase III studies that demonstrated the non-inferiority of once-daily dolutegravir + lamivudine to dolutegravir + tenofovir disoproxil fumarate/emtricitabine in achieving HIV-1 RNA <50 copies/mL at 48, 96, and 144 weeks in treatment-naive adults with HIV-1 infection. Objective: We present a post hoc analysis of the impact of treatment adherence on Week 48 virologic response. Methods: Adherence was estimated using pill counts and categorized as ≥90% vs <90%. Unadjusted treatment differences with exact 95% CIs were derived for the proportion of participants with HIV-1 RNA <50 copies/mL within each adherence category, using Snapshot algorithm and last available on-treatment viral load through Week 48. Results: In each treatment group, 5% of participants had <90% adherence (dolutegravir + lamivudine group, 35/716; dolutegravir + tenofovir disoproxil fumarate/emtricitabine group, 34/717). The proportion of participants with HIV-1 RNA <50 copies/mL (Snapshot) at Week 48 in the <90% adherence group was 69% in the dolutegravir + lamivudine group and 65% in the dolutegravir + tenofovir disoproxil fumarate/emtricitabine group (analysis by last on-treatment viral load: 91% and 85%, respectively). Corresponding proportions in the ≥90% adherence group were 93% and 96% (analysis by last on-treatment viral load: 97% and 99%, respectively). Conclusions: Decreased adherence resulted in lower Week 48 virologic efficacy outcomes that were comparable between treatment groups. These results indicate that the robust antiviral activity and regimen forgiveness of dolutegravir + lamivudine is similar to dolutegravir-containing 3-drug regimens (see graphical abstract). Graphical Abstract: UF0001